Recombination in liquid‐filled ionization chambers beyond the Boag limit. Issue 7 (14th June 2016) - Brualla‐González, L.; Aguiar, P.; González‐Castaño, D. M.; Gómez, F.; Roselló, J.; Pombar, M.; Pardo‐Montero, J.
Abstract : Purpose: The high mass density and low mobilities of charge carriers can cause important recombination in liquid‐filled ionization chambers (LICs). Saturation correction methods have been proposed for LICs. Correction methods for pulsed irradiation are based on Boag equation. However, Boag equation assumes that the charge ionized by one pulse is fully collected before the arrival of the next pulse. This condition does not hold in many clinical beams where the pulse repetition period may be shorter than the charge collection time, causing overlapping between charge carriers ionized by different pulses, and Boag equation is not applicable there. In this work, the authors present an experimental and numerical characterization of collection efficiencies in LICs beyond the Boag limit, with overlapping between charge carriers ionized by different pulses. Methods: The authors have studied recombination in a LIC array for different dose‐per‐pulse, pulse repetition frequency, and polarization voltage values. Measurements were performed in a Truebeam Linac using FF and FFF modalities. Dose‐per‐pulse and pulse repetition frequency have been obtained by monitoring the target current with an oscilloscope. Experimental collection efficiencies have been obtained by using a combination of the two‐dose‐rate method and ratios to the readout of a reference chamber (CC13, IBA). The authors have also used numerical simulation to complement the experimental data. Results: The authors have found that overlap significantly increases recombination in LICs, as expected. However, the functional dependence of collection efficiencies on the dose‐per‐pulse does not change (a linear dependence has been observed in the near‐saturation region for different degrees of overlapping, the same dependence observed in the nonoverlapping scenario). On the other hand, the dependence of collection efficiencies on the polarization voltage changes in the overlapping scenario and does not follow that of Boag equation, the reason being that changing the polarization voltage also affects the charge collection time, thus changing the amount of overlapping. Conclusions: These results have important consequences for saturation correction methods for LICs. On one hand, the two‐dose‐rate method, which relies on the functional dependence of the collection efficiencies on dose‐per‐pulse, can also be used in the overlapping situation, provided that the two measurements needed to feed the method are performed at the same pulse repetition frequency (monitor unit rate). This result opens the door to computing collection efficiencies in LICs in many clinical setups where charge overlap in the LIC exists. On the other hand, correction methods based on the voltage‐dependence of Boag equation like the three‐voltage method or the modified two‐voltage method will not work in the overlapping scenario due to the different functional dependence of collection efficiencies on the polarization voltage.